2012
DOI: 10.1159/000336822
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Induced Epithelial Mesenchymal Transformation

Abstract: Background: Progressive chronic kidney disease is often associated with albuminuria and renal fibrosis linked to the accumulation of myofibroblasts producing extracellular matrix. Renal myofibroblasts are derived from a number of cells including tubular epithelial cells (TECs) through epithelial mesenchymal transformation (EMT). This study explores the hypothesis that exposure of TECs to albumin induces EMT. Methods: Normal rat TECs (NRK52E) were exposed in culture to de-lipidated bovine serum albumin (dBSA; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…We showed, in an isolated system, free of hemodynamic influences, that albumin induces changes compatible with EMT, which is the most accepted pathophysiological mechanism to explain renal fibrosis in progressive renal disease. This important fact has been recently demonstrated in normal rat tubular cells NRK52E (27), and here we added that EMT may be prevented by bradykinin, an effect that is reversed by icatibant.…”
Section: Discussionsupporting
confidence: 62%
“…We showed, in an isolated system, free of hemodynamic influences, that albumin induces changes compatible with EMT, which is the most accepted pathophysiological mechanism to explain renal fibrosis in progressive renal disease. This important fact has been recently demonstrated in normal rat tubular cells NRK52E (27), and here we added that EMT may be prevented by bradykinin, an effect that is reversed by icatibant.…”
Section: Discussionsupporting
confidence: 62%
“…As expected, cellular treatment with albumin for 72 hr markedly increased the levels of α‐SMA, indicating the involvement of EMT in albumin‐induced renal injury. These findings are consistent with previous studies, which revealed a clear induction of EMT in rat renal tubular cells following exposure to albumin (Hu et al, ; Ibrini et al, ). A previous study showed that metformin treatment significantly suppresses albumin‐induced EMT in human proximal tubular cells (Lee et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Intriguingly, a direct association between albuminuria and EMT was reported. Studies in rat renal tubular cells revealed a clear induction of EMT − marked by a decrease in the levels of epithelial marker E‐cadherin and an increase in the expression of mesenchymal markers − α‐smooth muscle actin, fibroblast‐specific protein 1, and collagen I − following exposure to albumin (Hu et al, ; Ibrini et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence demonstrates that EMT is key in renal tubulointerstitial fibrosis (1,3). In the present study, a prolonged albumin overload model was used to mimic the effects of chronic proteinuria to induce EMT, the results demonstrated that there was a significant decrease in the viability of HKC cells exposed to HSA, and HSA treatment reduced the expression levels of the epithelial marker CK and increased the expression levels of the mesenchymal marker vimentin, suggesting that HSA induced EMT in HKC cells, which is consistent with the results of previous studies (16,17).…”
Section: Discussionsupporting
confidence: 90%